2007
DOI: 10.1029/2006ja012050
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic ion cyclotron waves instability threshold condition of suprathermal protons by kappa distribution

Abstract: [1] The well-known generalized Lorentzian (kappa) distribution generally provides a good representation for the high-energy tail population of natural cosmic suprathermal plasmas. In this study we examine the electromagnetic ion cyclotron waves (EMIC) instability driven by the temperature anisotropy condition (T ? /T k > 1) of suprathermal protons modeled with a typical kappa distribution in a cold multispecies plasma (electron, H + , He + , and O + ). Since the EMIC wave instability is found to be significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 51 publications
0
52
3
Order By: Relevance
“…This apparently disagrees with the previous results of Xiao et al (2007), who found a uniform increase of the anisotropy thresholds (at γ m /Ω p = 10 −3 , and 10 −2 ) with the increase of suprathermal protons. …”
Section: Emic Instability In Bi-kappa Plasmascontrasting
confidence: 57%
See 3 more Smart Citations
“…This apparently disagrees with the previous results of Xiao et al (2007), who found a uniform increase of the anisotropy thresholds (at γ m /Ω p = 10 −3 , and 10 −2 ) with the increase of suprathermal protons. …”
Section: Emic Instability In Bi-kappa Plasmascontrasting
confidence: 57%
“…An immediate conclusion is that a decrease of the powerindex κ must lower the anisotropy thresholds corresponding to the lowest EMIC growth rates (marginal conditions of instability, γ m → 0). But this evolution appears to disagree with the results of Xiao et al (2007), which are restrained only to a particular (magnetopsheric) plasma model with a fractional composition of four (dominant) cold components (electrons, H + (protons), He + , O + ) and a minor hot population of protons (relative density n h /n 0 0.15) .…”
Section: Introductioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Other extensions include inverse correlations using non-Maxwellian models by Xiao et al (2006Xiao et al ( , 2007, Lazar (2012); empirical inverse correlations for electrons and high-frequency instabilities by Gary et al (2005) and Š tverák et al (2008); modification of the inverse correlation by including binary collisional effects by ; efforts to rigorously calculate the inverse correlation by Isenberg (Isenberg 2012;Isenberg et al 2013) who sought to obtain a rigorous asymptotic solution of the plasma subjected to linear instability condition; including the effects of streaming population on the stability condition by Hadi et al (2014), , and Vafin et al (2015); the mutual dynamical influence of electrons and ions, considered by Michno et al (2014), Maneva et al (2016), and Shaaban et al (2016Shaaban et al ( , 2017, etc. Fig.…”
Section: Introductionmentioning
confidence: 99%